Experimental Paradigm for the Assessment of the Non-pharmacological Mechanism of Action in Medical Device Classification: The Example of Glycerine as Laxative - Sardi, Claudia; Garetto, Stefano; Capone, Laura; Galbiati, Valentina; Racchi, Marco; Govoni, Stefano; Giovagnoni, Emiliano; Lucci, Jacopo (Frontiers in Pharmacology, 2018)
The evolution of medical devices has led to the introduction of medical devices that include “substances” and which, due to their presentation and sites of application may resemble medicinal products. The difference between substance-based medical devices and medicinal products lies in the proper definition of the principal mechanism of action. The major problem at the moment is the lack of a proper procedure for the demonstration of a mechanism that is “not pharmacological, immunological or metabolic.” We aimed to design an experimental set up to demonstrate the difference between the mechanism of action of two substances used commonly for the treatment of constipation, lubiprostone (example of medicinal product) and glycerine (example of medical device). By implementing cellular models and molecular analyses we demonstrate the difference in their mechanism of action. This set up can be considered an example on the possibility to define a paradigm for the case by case study of the mechanism of action of substances and combination of substances in medical devices.